Provision of multilevel public goods through positive externalities: Experimental evidence - Werner Güth; Lauri Sääksvuori (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The provision of public goods regularly embodies interrelated spheres of influence on multiple scales. This article examines the nature of human behavior in a multilevel social dilemma game with positive provision externalities to local and global scales. We report experimental results showing that the behavior in multilevel games is strongly driven by asymmetric conditional cooperation prioritizing local level externalities. Our findings demonstrate how individuals adjust their behavior over time to local conditions. We do not find significant adjustment to the global group average, suggesting that the local group creates a salient reference group for social comparisons in multilevel public goods provision. Our results emphasize the importance of building strong local level commitment when designing institutional responses to promote sustainable provision of globally important public goods like the global climate.
Keywords: H41; C72; C91; C92; 330; experiment; groups; public good; spillover game; transboundary effects; Öffentliches Gut; Versorgung; Nichtkooperatives Spiel; Spillover-Effekt; Dynamisches Spiel; Externer Effekt; Soziale Beziehungen; Soziale Gruppe; Test; Klimaschutz